New approach to estimating variability in visual field data using an image processing technique. Issue 3 (March 1995) - Crabb, D P; Edgar, D F; Fitzke, F W; McNaught, A I; Wynn, H P
Abstract : AIMS–A new framework for evaluating pointwise sensitivity variation in computerised visual field data is demonstrated. METHODS–A measure of local spatial variability (LSV) is generated using an image processing technique. Fifty five eyes from a sample of normal and glaucomatous subjects, examined on the Humphrey field analyser (HFA), were used to illustrate the method. RESULTS–Significant correlation between LSV and conventional estimates–namely, HFA pattern standard deviation and short term fluctuation, were found. CONCLUSION–LSV is not dependent on normals' reference data or repeated threshold determinations, thus potentially reducing test time. Also, the illustrated pointwise maps of LSV could provide a method for identifying areas of fluctuation commonly found in early glaucomatous field loss.